Disease Extent at Secondary Cytoreductive Surgery is Predictive of Progression-free and Overall Survival in Advanced Stage Ovarian Cancer: an NRG Oncology/Gynecologic Oncology Group study - Rose, Peter G. (Gynecol Oncol, 2016)
PURPOSE: GOG 152 was a randomized trial of secondary cytoreductive surgery (SCS) in patients with suboptimal residual disease (residual tumor nodule >1 cm in greatest diameter) following primary cytoreductive surgery for advanced stage ovarian cancer. The current analysis was undertaken to evaluate the impact of disease findings at SCS on progression-free survival (PFS) and overall survival (OS). METHODS: Among the 550 patients enrolled on GOG-152, two-hundred-sixteen patients were randomly assigned following 3 cycles of cisplatin and paclitaxel to receive SCS. In 15 patients (7%) surgery was declined or contraindicated. In the remaining 201 patients the operative and pathology reports were utilized to classify their disease status at the beginning of SCS as; no gross disease/microscopically negative N= 40 (19.9%), no gross disease/microscopically positive N= 8 (4.0%), and gross disease N=153 (76.1%). RESULTS: The median PFS for patients with no gross disease/microscopically negative was 16.1 months, no gross disease/microscopically positive was 13.5 months and for gross disease was 11.7 months, p=0.002. The median OS for patients with no gross disease/microscopically negative was 51.5 months, no gross disease/microscopically positive was 42.6 months and for gross disease was 34.9 months, p=0.018. CONCLUSION: Although as previously reported SCS did not change PFS or OS, for those who underwent the procedure, their operative and pathologic findings were predictive of PFS and OS. Surgical/pathological residual disease is a biomarker of response to chemotherapy and predictive of PFS and OS.